The Effectiveness of Using The Speech Skill Strategy to Entertain The Skill of Speaking Arabic - Qurrotul Faizah; Nazilatil Maghviroh (STAI Nurul Huda Kapongan Situbondo, 2022)
This study uses an experimental research method used in this study to find the effect of some treatments on others under controlled conditions. then one student in the “good” category with a score of 6.7%. And 0 students in the very good category are 0%.Speaking ability Students of the experimental class using the speech skill strategy showed that up to. 0 students were in the 0 needing guidance category, then there were up to 0 female students in the 0 Good Enough category, then 7 students were in the 46.7% Good category. And 8 students in the very good category, with a rate of 53.3%. Thus, it can be concluded that the ability to speak the Arabic language among experimental class students using the speech skill strategy in the eleventh class of Alia Nour Al-Huda School for Girls has a medium value. from 0.067